Cutting force and wear behaviour of a brazed diamond trepanning bit when drilling granite. (7th January 2022) - Sun, Baojun; Jiang, Chengjie; Zong, Fule
A brazed diamond trepanning bit was developed and used to drill granite. Assessment of the cutting performance of the bit included studying the cutting forces, torque, wear behaviour of abrasive grains, and service life. These results are compared to the results obtained with the electroplated diamond bit. It was found that the drilling force of the bit is related to the cutting thickness of a single abrasive particle and to the number of abrasive particles arranged on the end face of the bit. For the same size, abrasive arrangement, and cutting parameters, the drilling force decreases with an increase in the spindle speed and increases with an increase in the feed rate. Also, the service life of the brazed bit is larger than that of the electroplated bit. The failure form of the brazed bit is mechanical wear, whereas the failure form of the electroplated bit is abrasive shedding.